(untitled) (Philosophy and Progress, 2019)
Confucius (551-479 BC) is considered to be a great philosopher and educator in Chinese society and one of the greatest scholars ever in world history. He was the founder of Confucianism, which constitutes a major part of traditional Chinese culture and made tremendous contribution to the unfolding of Chinese civilization over the centuries. In this study, the authors have presented a comprehensive outline of Confucianism and have attempted to gauge the attitude of contemporary Chinese people towards Confucian concepts, values and attributes as well as their influences on the social lives of present-day Chinese population. The Likert Scale was applied in the study to assess the attitude of the Chinese educated class belonging to the educational institutions like the universities in Beijing towards Confucianism. It was found from the survey that the Confucian concepts still wield substantial influence on the social outlook of the modern-day Chinese people and these attributes are still relevant in the day to day lives of the Chinese society. Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 109-132